Narcotics Anonymous attendees' perceptions and experiences of substitute behaviors in the Western Cape, South Africa - Deborah Louise Sinclair; Steve Sussman; Shazly Savahl; Maria Florence; Wouter Vanderplasschen (BMC, 2023)
Abstract Background Much remains unknown about the dynamics of substitute behaviors during addiction recovery among persons attending recovery support groups. Insight into the nature, motives for, and course of substitute behaviors could help to shape recovery support and harm reduction services. Methods Twenty-three semi-structured in-depth interviews (n = 14 males and n = 9 females) were conducted with a convenience sample of Narcotics Anonymous attendees from a number of groups in the Western Cape, South Africa. Participants ranged in age from 22-55 years (M = 39.3, SD = 9.35). Results Thematic analysis yielded four themes: (i) substance-to-substance substitution; (ii) substance-to-behavior substitution; (iii) substitute behaviors and harm (reduction) and (iv) support needs to manage and resolve substitute behaviors. According to the study, participants' substitute behaviors developed across recovery stages; were temporary or long-term replacements for substance use disorders and were engaged for distraction, isolation from others, calming, assuaging boredom, keeping occupied, filling a perceived experiential void, modifying mood and to self-medicate. While substitutes were utilized for harm reduction or relapse prevention, the potential for ostensibly healthy behaviors to threaten recovery and lead to relapse was also recognized. Conclusions Self-monitoring, ongoing vigilance, and awareness of when substitutes become genuine addictions are critical for timely, suitable interventions.